My sign name is 'Rising Sun' Plurilingual and multimodal teaching with deaf and hearing migrants - Sabina Fontana (University of Bologna, 2020)
The contribution presents the results of a field study on plurilingual multimodal teaching to Deaf migrants based on written Italian/Italian Sign Language (LIS). Early results, experiences, methods and the background theories (Fontana e Mignosi, 2020; Pienemann, 1998) will be presented in order to show how teaching paths should overcome traditional approaches and take into account the multimodality in communication and in the relationships. Starting from the results of these research, hypothesis on a syllabus will be proposed, which will be built on educational accessibility and will use approaches based on translanguaging (Garcia e Wei, 2015) and on trasformative action research (Stevenson, 1995). Such research show learners seem to benefit of a teaching approach based on intercorporeity and multimodality, which promotes an active role of participants.